2014
DOI: 10.1007/s13277-014-2546-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-25 promotes ovarian cancer proliferation and motility by targeting LATS2

Abstract: Ovarian cancer (OC) is a major cancer-related mortality among women. Recent studies suggest that many microRNAs (miRNAs) were dysregulated and involved in tumorigenesis of OC. The present study investigated the role of miR-25 in the development and progression of OC. The expression of miR-25 was increased in OC tissues and cell lines. Inhibition of miR-25 remarkably suppressed proliferation, migration, and invasion of OC cells. Large tumor suppressor 2 (LATS2), a tumor suppressor, was confirmed to be a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 25 publications
1
48
0
1
Order By: Relevance
“…Moreover, many miRNAs, such as miR-25, miR-181b, and miR-93, suppressed LATS2 at the posttranscription level by directly binding to its mRNA in multiple cancer cells (41)(42)(43). Our results demonstrated that LATS2 could be regulated at the transcriptional level through histone modification mediated by lncRNA PVT1 and PRC2.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, many miRNAs, such as miR-25, miR-181b, and miR-93, suppressed LATS2 at the posttranscription level by directly binding to its mRNA in multiple cancer cells (41)(42)(43). Our results demonstrated that LATS2 could be regulated at the transcriptional level through histone modification mediated by lncRNA PVT1 and PRC2.…”
Section: Discussionmentioning
confidence: 66%
“…Such a reduction in the mRNA expression of LATS2 is likely to be induced by mechanisms other than promoter hypermethylation. Previously, several micoRNAs, including microRNA (miR)93 in breast cancer (13), miR25 in ovarian cancer (14) and miR31 in lung (15) and endometrial cancer (16), have been reported to directly target the LATS2 gene and reduce its anti-oncogenic effect. A previous study identified a LATS2 mutation, which can reduce the expression of the gene in lung cancer, however, such a mutation in breast cancer remains to be elucidated (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their small size and influence in a broad range of biological processes, miRNAs are very attractive therapeutic targets for GBM. miR-25 is one of the most overexpressed miRNAs in a number of profiling experiments designed for the detection of miRNAs dysregulated in human cancers [16][17][18][19][20][21][22][23][24][25]29]. Li et al reported that miR-25 promoted gastric cancer migration, invasion, and proliferation by directly targeting transducer of ERBB2 and 1 and correlated with poor survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25]. However, the role of miR-25 in glioblastoma tumorigenesis and the underlying molecular mechanisms by which miR-25 exerts its functions had remained-until recently-largely unknown.…”
Section: Introductionmentioning
confidence: 99%